2005
DOI: 10.1007/s11060-004-7316-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of Interferon Regulatory Factor (IRF)-1 and IRF-2 in Diffusely Infiltrating Astrocytomas (DIA): Response to Interferon (IFN)-β in Glioblastoma Cells and Prognostic Value for DIA

Abstract: The precise mechanisms governing the direct effect of IFN-beta, including apoptosis induction, are not yet fully understood. To gain a better insight into these mechanisms, we investigated the signaling pathways focusing particularly on interferon regulatory factor 1 (IRF-1) and IRF-2 in glioblastoma cell lines. Furthermore, we attempted to determine whether or not IRF-1 and IRF-2 act as additional prognostic indicators in diffusely infiltrating astrocytomas (DIA). We first assessed the cytotoxic effects of IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Furthermore, statistical data indicated that IRF-2 expression was tightly correlated with disease progression in esophageal cancer. 16 Moreover, besides the association between high-level IRF-2 expression and improved survival in univariate analyses, other of our findings argue against an oncogenic role of IRF-2 in ovarian cancer: (i) in contrast to other solid tumors such as diffusely infiltrating astrocytomas, breast and as already mentioned esophageal cancers, 16,18,19 the expression of IRF-2 was not found to be upregulated in either ovarian cancer tissue or established ovarian cancer cell lines, (ii) significantly higher levels of IRF-2 mRNA were found in early-stage when compared with advanced-stage ovarian cancers, and (iii) IRF-2 expression was inversely related to residual disease after primary debulking surgery. Concerning the latter point, there is excellent evidence to show that ovarian cancers, whose complete surgical clearance is impossible at primary surgery, exhibit a more aggressive phenotype with a completely different molecular signature than do cancers allowing optimal cytoreduction.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, statistical data indicated that IRF-2 expression was tightly correlated with disease progression in esophageal cancer. 16 Moreover, besides the association between high-level IRF-2 expression and improved survival in univariate analyses, other of our findings argue against an oncogenic role of IRF-2 in ovarian cancer: (i) in contrast to other solid tumors such as diffusely infiltrating astrocytomas, breast and as already mentioned esophageal cancers, 16,18,19 the expression of IRF-2 was not found to be upregulated in either ovarian cancer tissue or established ovarian cancer cell lines, (ii) significantly higher levels of IRF-2 mRNA were found in early-stage when compared with advanced-stage ovarian cancers, and (iii) IRF-2 expression was inversely related to residual disease after primary debulking surgery. Concerning the latter point, there is excellent evidence to show that ovarian cancers, whose complete surgical clearance is impossible at primary surgery, exhibit a more aggressive phenotype with a completely different molecular signature than do cancers allowing optimal cytoreduction.…”
Section: Discussionmentioning
confidence: 50%
“…Subsequently, it was shown to exhibit pleiotropic biological activities including immunomodulatory activity, anti-angiogenetic activity and direct antitumor effects, e.g. growth inhibition and apoptosis (30)(31)(32). In addition to such multiple functions of IFN-ß against human neoplasias, it acts as a drug sensitizer enhancing the toxicity against a variety of neoplasias when administered in combination with nitrosoureas (alkylating agents) (33).…”
Section: Introductionmentioning
confidence: 99%
“…Although IRF-2 has previously been related to apoptosis regulation (34,35,58), the mechanism still remains unclear. In this study, we show that the lack of IRF-2 renders macrophages significantly more sensitive to apoptotic stimuli, supporting our previous observations that Kupffer cells from IRF-2 Ϫ/Ϫ mice are more sensitive to apoptosis basally and after LPS (34).…”
Section: Discussionmentioning
confidence: 99%